POLITICAL MARKETING AND DEMOCRACY: CRITICAL REFLECTIONS - Pešić, Milena; Vujanović, Jelena (Political Review, 2025)
The subject of research in this paper is political marketing, which is critically examined from the standpoint of the interests of democracy. Guided by the goal of identifying key problems raised by its widespread application in political life, we have used methods of analysis and evaluation of critical considerations of the effects of political marketing on the democratic process. As the assumed normative background of these critical observations, we have used certain principles and requirements of two, in many ways opposite, concepts: the concept of competitive elitism and deliberative democracy, and the pluralistic understanding as a kind of “middle way”. We synthesized the critical considerations in several general critical remarks. The first remark refers to the phenomenon of the marketization of politics, i.e. changes in the way politics is understood and functions, subject to the consumer forces of business management and the market. This is about the increase in populism in politics due to the prevalence of the “follower mentality”, the weakening of leadership, the focus on short-term solutions instead of what is right for society in the long term. Political marketing also contributes to the fact that politics is increasingly losing its content – ​​political communication and party politics are less and less directly related to political issues and beliefs, and more and more to individuals, personality, image, brand. The phenomenon of personalization, through pseudo-intimacy with citizens, distracts attention from essential political issues. The second remark develops the implications of understanding politics as the buying and selling and commodification of public opinion, which ignores the way in which ideas and values ​​are key to the democratic process, as the foundation of competing visions of improving politics in order to achieve a better society. The instrumental approach to democracy limits critical-rational debate in the public sphere, reducing democracy to a method for achieving particular goals, by strengthening the functional role of voters in relation to parties, reducing them to a means of achieving party goals. Political consumerism, on the other hand, threatens traditional notions of citizenship, because it leads to selfish calculations becoming decisive in voting, suppressing the idea of ​​the general interest of which commodified public opinion becomes incapable. The third objection relates to changes in the character of the political offer driven by the imperatives of its attractiveness to the political market and research on public opinion preferences. The last remark is directed at the formation of the attitudes of citizens as political consumers, under the influence of marketing political communication guided by predictive modeling methods and supplied with propaganda-manipulative techniques. In conclusion, the paper presents some of the ideas of the critical agenda of political marketing, as a possible framework for the development of its assessment and subjection to democratic control, with the theoretical and methodological support of a critical analysis of political discourse.